Combining Adult Learning Theory with Occupational Therapy Intervention for Bladder and Bowel Management after Spinal Cord Injury: A Case Report. Issue 2 (2nd April 2016) - Gallagher, Gina; Bell, Alison
ABSTRACT: Bladder and bowel management is an important goal of rehabilitation for clients with spinal cord injury. Dependence is these areas have been linked to a variety of secondary complications, including decreased quality of life, urinary tract infections and pressure ulcers (Hammell, 2010; Hicken et al, 2001). Occupational therapists have been identified as important members of the health care team in spinal cord injury rehabilitation; however, specific roles and interventions have not been clearly described. This case report will describe occupational therapy interventions embedded with principles of adult learning theory to address bladder and bowel management with an adult client who sustained an incomplete thoracic level spinal cord injury.